UPAYA SATUAN INTELKAM DALAM DETEKSI DINI GUNA PENGGALANGAN KEGIATAN KELOMPOK RADIKAL DI WILAYAH HUKUM POLRES SUKOHARJO - MARCO DIMARA (Indonesian Journal of Police Studies, 2022)
ABSTRACT EFFORTS OF THE INTELKAM UNIT IN EARLY DETECTION TO RAISE RADICAL GROUP ACTIVITIES IN THE JURISDICTION OF THE SUKOHARJO POLICE Marco millian dimara,18.220,marcoakpol123@gmail.com The background of this study was carried out because there are many people of Sukoharjo Regency who follow radicalism by joining a radicalism group and boarding school and former terrorism convicts in Sukoharjo Regency. Research conducted using a qualitative approach, namely researchers go directly into the field to study and explore phenomena that occur in the field in accordance with problems. This research focuses on the fundraising of Satintelkam Polres Sukoharjo. The data sources used are primary data and secondary data.To measure the accuracy of the data, data triangulation is carried out. Then in data analysis techniques are carried out through data reduction, data presentation and conclusion withdrawal. The results of the research that has been obtained show that the early detection activities carried out by satintelkam polres Sukoharjo are carried out to raise radical group activities. In the implementation of this investigation is not in accordance with Perkabik No. 3 of 2013. In the implementation of the investigation there are still factors that affect both internally and externally. The conclusion of the implementation of the Sukoharjo Police Satintelkam fundraising is that the implementation of the investigation has not been carried out optimally because it is not guided by Perkabik No.3 of 2013 which is an SOP regarding intelligence investigations. Keywords : Effort – early detection - Satintelkam – Fundraising - Satintelkam